Oxidative stress pathways involved in cytotoxicity and genotoxicity of titanium dioxide (TiO2) nanoparticles on cells constitutive of alveolo-capillary barrier in vitro. (June 2016) - Hanot-Roy, Maïté; Tubeuf, Emilie; Guilbert, Ariane; Bado-Nilles, Anne; Vigneron, Pascale; Trouiller, Bénédicte; Braun, Anne; Lacroix, Ghislaine
Abstract: The health risks of nanoparticles remain a serious concern given their prevalence from industrial and domestic use. The primary route of titanium dioxide nanoparticle exposure is inhalation. The extent to which nanoparticles contribute to cellular toxicity is known to associate induction of oxidative stress. To investigate this problem further, the effect of titanium dioxide nanoparticles was examined on cell lines representative of alveolo-capillary barrier. The present study showed that all nanoparticle-exposed cell lines displayed ROS generation. Macrophage-like THP-1 and HPMEC-ST1.6R microvascular cells were sensitive to endogenous redox changes and underwent apoptosis, but not alveolar epithelial A549 cells. Genotoxic potential of titanium dioxide nanoparticles was investigated using the activation of γH2AX, activation of DNA repair proteins and cell cycle arrest. In the sensitive cell lines, DNA damage was persistent and activation of DNA repair pathways was observed. Moreover, western blot analysis showed that specific pathways associated with cellular stress response were activated concomitantly with DNA repair or apoptosis. Nanoparticles-induced oxidative stress is finally signal transducer for further physiological effects including genotoxicity and cytotoxicity. Within activated pathways, HSP27 and SAPK/JNK proteins appeared as potential biomarkers of intracellular stress and of sensitivity to endogenous redox changes, respectively, enabling to predict cell behavior. Highlights: Nanoparticle-exposed cell lines showed ROS generation, a common toxicity mechanism. Alveolar epithelial A549 were resistant to nanoparticle exposure. HPMEC-ST1.6R and THP-1 cells were sensitive to endogenous redox changes. Correlation between cyto- and geno-toxicological endpoints and oxidative stress activated pathways HSP27 and SAPK/JNK proteins were potential markers to predict cell response.